2022
DOI: 10.1167/tvst.11.8.22
|View full text |Cite
|
Sign up to set email alerts
|

Pointwise Visual Field Estimation From Optical Coherence Tomography in Glaucoma Using Deep Learning

Abstract: Purpose Standard automated perimetry is the gold standard to monitor visual field (VF) loss in glaucoma management, but it is prone to intrasubject variability. We trained and validated a customized deep learning (DL) regression model with Xception backbone that estimates pointwise and overall VF sensitivity from unsegmented optical coherence tomography (OCT) scans. Methods DL regression models have been trained with four imaging modalities (circumpapillary OCT at 3.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Other information (other data from VF testing such as pattern deviation, location of VF loss, and more medical history) may be helpful in glaucoma management and may be displayed in other ways, such as dynamic user interfaces. In addition, the incorporation of point-wise predictions of VF 55,56 may assist in increasing clinician trust in the predicted VF. However, these will require future iterations of GLANCE and may be implemented as part of future stakeholder interviews and data reviews.…”
Section: Discussionmentioning
confidence: 99%
“…Other information (other data from VF testing such as pattern deviation, location of VF loss, and more medical history) may be helpful in glaucoma management and may be displayed in other ways, such as dynamic user interfaces. In addition, the incorporation of point-wise predictions of VF 55,56 may assist in increasing clinician trust in the predicted VF. However, these will require future iterations of GLANCE and may be implemented as part of future stakeholder interviews and data reviews.…”
Section: Discussionmentioning
confidence: 99%
“…We also observed that estimation performance in the external test set was better compared with the internal test set, which could be attributed to differences in the spatial distribution of focal severities in the two test sets. Strengths of our study include the use of a standardized, stratified approach for dataset construction, the There has been continued interest in the development and evaluation of models for the estimation VF loss in glaucoma from structural measurements of the retina [9][10][11][12][13][14]27,28 with reported MAEs in the range of 2-5 dB [11][12][13][14] for VF MD estimation. In most previous studies, comparisons with other approaches were largely limited to linear regression 9,11,12,28 or SVMs.…”
Section: Discussionmentioning
confidence: 99%
“…95% confidence intervals were obtained using a clustered bootstrapping approach at the subject level to adjust for intrasubject correlations. Baseline MAEs were calculated with the differences between the actual values and the means of the datasets, and the extent by which the baseline MAEs were reduced with each of the models was also calculated 14 . For the global VF MD analysis, an additional linear regression (LR) model using global RNFL values was also developed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemelings et al used the raw circumpapillary rings at three different diameters as input to a customized deep learning model [27]. As a baseline model, the corresponding enface scanning laser ophthalmoscopy image was used.…”
Section: Visual Field Estimation With Artificial Intelligencementioning
confidence: 99%